Early microbial colonization affects DNA methylation of genes related to intestinal immunity and metabolism in preterm pigs. (19th January 2018) - Pan, Xiaoyu; Gong, Desheng; Nguyen, Duc Ninh; Zhang, Xinxin; Hu, Qi; Lu, Hanlin; Fredholm, Merete; Sangild, Per T; Gao, Fei
Abstract: Epigenetic regulation may play an important role in mediating microbe–host interactions and adaptation of intestinal gene expression to bacterial colonization just after birth. This is particularly important after preterm birth because the immature intestine is hypersensitive to invading bacteria. We compared the intestinal DNA methylome and microbiome between conventional (CON) and antibiotics-treated (AB) preterm pigs, used as a model for preterm infants. Oral AB treatment reduced bacterial density (∼100-fold), diversity and fermentation, improved the resistance to necrotizing enterocolitis (NEC) and changed the genome-wide DNA methylation in the distal small intestine. Integration of epigenome data with previously obtained proteome data showed that intestinal immune–metabolic pathways were affected by the AB-induced delay in bacterial colonization. DNA methylation and expression of intestinal genes, related to innate immune response, phagocytosis, endothelial homeostasis and tissue metabolism (e.g. CPN1, C3, LBP, HIF1A, MicroRNA-126, PTPRE), differed between AB and CON pigs even before any evidence of NEC lesions. Our findings document that the newborn immature intestine is influenced by bacterial colonization via DNA methylation changes. Microbiota-dependent epigenetic programming of genes related to gut immunity, vascular integrity and metabolism may be critical for short- and long-term intestinal health in preterm neonates.